2021
DOI: 10.3390/ijms222212496
|View full text |Cite
|
Sign up to set email alerts
|

Cell Behavior of Non-Small Cell Lung Cancer Is at EGFR and MicroRNAs Hands

Abstract: Lung cancer is a complex disease associated with gene mutations, particularly mutations of Kirsten Rat Sarcoma Viral Oncogene Homolog (KRAS) and epidermal growth factor receptor (EGFR). Non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC) are the two major types of lung cancer. The former includes most lung cancers (85%) and are commonly associated with EGFR mutations. Several EGFR-tyrosine kinase inhibitors (EGFR-TKIs), including erlotinib, gefitinib, and osimertinib, are effective therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 237 publications
(350 reference statements)
0
10
0
Order By: Relevance
“…Several studies underscored the clinical significance of miRNAs serving as diagnostic, prognostic, and predictive markers for a wide range of tumor entities [ 132 , 133 ]. Mechanistically, dysregulated miRNA expression via regulation of their targets can affect hallmarks of cancer, namely cell proliferation, apoptosis, adhesion, migration, invasion, and metastasis, as is evident from both in vitro and in vivo studies [ 129 , 134 , 135 , 136 , 137 , 138 ].…”
Section: Microrna-dependent Syndecan Regulation and Breast Cancermentioning
confidence: 99%
“…Several studies underscored the clinical significance of miRNAs serving as diagnostic, prognostic, and predictive markers for a wide range of tumor entities [ 132 , 133 ]. Mechanistically, dysregulated miRNA expression via regulation of their targets can affect hallmarks of cancer, namely cell proliferation, apoptosis, adhesion, migration, invasion, and metastasis, as is evident from both in vitro and in vivo studies [ 129 , 134 , 135 , 136 , 137 , 138 ].…”
Section: Microrna-dependent Syndecan Regulation and Breast Cancermentioning
confidence: 99%
“…Acquired drug resistance has long been a major hurdle hindering the therapeutic effect of EGFR TKIs [ 6 , 7 , 8 ]. Accumulating evidence has indicated that ncRNAs, especially circRNAs, lncRNAs and miRNAs, play a vital role in EGFR TKI-resistant lung cancer via alternative signaling pathway modulation [ 10 , 36 ]. Here, ncRNAs involved in essential signaling pathways downstream and parallel pathways of EGFR are discussed in detail ( Figure 2 ).…”
Section: Mechanisms Of Ncrnas Involved In Egfr Tki Resistancementioning
confidence: 99%
“…In cancer biology, NF-κB has major functions as a proliferative stimulator and apoptotic suppressor in tumor cells, which also mediates drug resistance [ 70 ]. Notably, NF-κB not only independently sustains EGFR TKI resistance but also serves as an effector downstream of the JAK/STAT signaling pathway to enhance EGFR TKI resistance [ 36 ]. NcRNAs involved in NF-κB pathway modulation are primarily examined for their ability to target upstream regulators.…”
Section: Mechanisms Of Ncrnas Involved In Egfr Tki Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…These aberrations induce cancer cells to stimulate adjacent stromal cells and augment the release of ECM proteins, growth factors, cytokines, angiogenic factors, and proteolytic enzymes into tumor stroma to form a tumor-supportive microenvironment ( Figure 1 ) ( 20 , 21 ). The development of resistance to EGFR tyrosine kinase inhibitors (TKIs) is still a critical problem in lung cancer, and the underlying mechanisms remain fully unexplored ( 22 ). Although TKI-induced or –selected genetic alterations are known to cause chemoresistance, other poorly understood mechanisms in tumor cells can drive this resistance.…”
Section: Introductionmentioning
confidence: 99%